Herschel Observations of Disks around Late-type Stars. (16th June 2020) - Tanner, Angelle; Plavchan, Peter; Bryden, Geoff; Kennedy, Grant; Matrá, Luca; Cronin-Coltsmann, Patrick; Lowrance, Patrick; Henry, Todd; Riaz, Basmah; Gizis, John E.; Riedel, Adric; Choquet, Elodie
Abstract: A set of twenty late-type (K5-M5) stars were observed with the Herschel Space Observatory at 100 and 160 microns with the goal of searching for far-infrared excesses indicative of the presence of circumstellar disks. Out of this sample, four stars (TYC 7443-1102-1, TYC 9340-437-1, GJ 784 and GJ 707) have infrared excesses above their stellar photospheres at either 100 or 160 μ m or both. At 100 microns TYC 9340-437-1 is spatially resolved with a shape that suggests it is surrounded by a face-on disk. The 100 μ m excess flux associated with GJ 707 is marginal at around 3 σ . The excess flux associated with GJ 784 is most likely due to a background galaxy as the dust radius estimated from the spectral energy fit implies that any associated dust disk should have been resolved in the Herschel images but is not. TYC 7443-1102-1 has been observed with ALMA which resolves the emission at its location into two distinct sources making the Herschel excess most likely also due to a background galaxy. It is worth noting that this star is in the 23 Myr old β Pic association. With a disk luminosity on the order of 10 −3 L *, this system is an ideal follow-up target for high-contrast imaging and ALMA.